Stress-induced electronic structure modulation of manganese-incorporated Ni2P leading to enhanced activity for water splitting - Sarkar, Shreya; Dheer, Lakshay; Vinod, C. P.; Thapa, Ranjit; Waghmare, V. Umesh; Peter, Sebastian C. (ACS Applied Energy Materials, 2020)
The cornerstone of the emerging hydrogen economy is hydrogen production by water electrolysis with concomitant oxygen generation. Incorporating a third element in metal phosphides can tune the crystalline and electronic structure, hence improving the electrocatalytic properties. In this work, Mn-doped Ni2P with varying ratios of Mn and Ni has been explored as excellent catalysts for water splitting. A complete cell made of the best catalyst Ni1.5Mn0.5P electrodes showed low voltage of 1.75 V at a current density of 10 mA cm(-2) due to enhanced electrical conductivity, induction of tensile stress, enhanced electrochemical surface area, and increased electric dipole upon Mn incorporation.
Keywords: Electronic Structure; hydrogen evolution reaction; Oxygen Evolution Reaction; phosphides; water splitting

Structure-tailored non-noble metal-based ternary chalcogenide nanocrystals for pt-like electrocatalytic hydrogen production - Sarkar, Shreya; Rawat, Abhishek; Das, Tisita; Gaboardi, Mattia; Chakraborty, Sudip; Vinod, C. P.; Peter, Sebastian C. (ChemSusChem, 2021)
A facile microwave-assisted strategy was employed to synthesize Ni3Bi2S2 nanocrystals. Variation in the synthesis conditions tuned the composition of monoclinic and orthorhombic phases of Ni3Bi2S2. The electrochemical hydrogen evolution activity of the catalyst with highest percentage of monoclinic phase demonstrated a negligible onset potential of only 24 mV close to that of state-of-the-art Pt/C with an overpotential as low as 88 mV. Density functional theory calculations predicted the monoclinic phase exhibit the lowest adsorption free energy corresponding to hydrogen adsorption (Delta GadsH*) and, therefore, the highest hydrogen evolution activity amongst the considered phases. The quasi-2D structure of monoclinic phase facilitated an increased charge-transfer between Ni and Bi, favoring the downward shift of the d-band center to enhance the catalytic activity.
Keywords: charge transfer; electrocatalysis; hydrogen evolution reaction; Nanomaterials; ternary chalcogenides

Strain-enhanced phase transformation of iron oxide for higher alcohol production from CO2 - Goud, Devender; Churipard, Sathyapal R.; Bagchi, Debabrata; Singh, Ashutosh Kumar; Riyaz, Mohd; Vinod, C. P.; Peter, Sebastian C. (ACS Catalysis, 2022)
Conversion of CO2 to higher alcohols (HAs) and higher hydrocarbons (HCs) has a greater advantage compared to C1 products because of their high energy density and wide range of applications in daily life. Despite the immense potential of these chemicals, not much of scientific research has been focused on the conversion of CO2 to HAs. In the present work, we have introduced the concept of strain in designing the material to enhance the CO(2 )to HA performance. We introduced strain in a traditional iron-based catalyst, Fe2O3, by the introduction of indium (In), which facilitates the selective conversion of CO2 to HA. An optimum strain favored a 36.7% CO2 conversion with a 42% HA selectivity, and a record yield of 15.42%. The strain has been tuned further with the introduction of K as a promoter. The introduced strain upon In substitution and K promotion favored the conversion of CO2, which is mapped by powder X-ray diffraction, X-ray photoelectron spectroscopy, and X-ray absorption spectroscopy. Further, the change in the mechanism upon In incorporation and K promotion has been probed by in situ diffuse reflectance infrared fourier transform spectroscopy, and it is found that the OCHx intermediate, which produces HAs, is more prominent upon In substitution, which favored the enhancement of HA production compared to that of pristine Fe2O3.
Keywords: CO2 to HA; Fischer-Tropsch synthesis (FTS); Phase transformation; reverse water gas shift (RWGS) reaction; strain

Structure-tailored surface oxide on Cu-Ga intermetallics enhances CO2 reduction selectivity to methanol at ultralow potential - Bagchi, Debabrata; Raj, Jithu; Singh, Ashutosh Kumar; Cherevotan, Arjun; Roy, Soumyabrata; Manoj, Kaja Sai; Vinod, C. P.; Peter, Sebastian C. (Advanced Materials, 2022)
Electrochemical CO2 reduction reaction (eCO(2)RR) is performed on two intermetallic compounds formed by copper and gallium metals (CuGa2 and Cu9Ga4). Among them, CuGa2 selectively converts CO2 to methanol with remarkable Faradaic efficiency of 77.26% at an extremely low potential of -0.3 V vs RHE. The high performance of CuGa2 compared to Cu9Ga4 is driven by its unique 2D structure, which retains surface and subsurface oxide species (Ga2O3) even in the reduction atmosphere. The Ga2O3 species is mapped by X-ray photoelectron spectroscopy (XPS) and X-ray absorption fine structure (XAFS) techniques and electrochemical measurements. The eCO(2)RR selectivity to methanol are decreased at higher potential due to the lattice expansion caused by the reduction of the Ga2O3, which is probed by in situ XAFS, quasi in situ powder X-ray diffraction, and ex situ XPS measurements. The mechanism of the formation of methanol is visualized by in situ infrared (IR) spectroscopy and the source of the carbon of methanol at the molecular level is confirmed from the isotope-labeling experiments in presence of (CO2)-C-13. Finally, to minimize the mass transport limitations and improve the overall eCO(2)RR performance, a poly(tetrafluoroethylene)-based gas diffusion electrode is used in the flow cell configuration.
Keywords: (2) reduction; CO; Electrochemistry; Methanol